Disparities in Healthcare Access: Addressing Systemic Barriers in Urban and Rural Communities - Afni, Nur (Journal of Health Literacy and Qualitative Research, 2023)
Healthcare disparities between urban and rural areas pose significant public health challenges, affecting healthcare accessibility, quality, and outcomes. This study systematically reviews the factors contributing to these disparities, including socioeconomic status, geographic barriers, healthcare infrastructure, and workforce distribution. A comprehensive literature search was conducted across major academic databases, focusing on peer-reviewed studies examining urban-rural healthcare inequalities and potential interventions. Findings indicate that rural populations experience limited access to healthcare due to inadequate medical facilities, long travel distances, and a shortage of healthcare professionals. Socioeconomic determinants, such as lower income and education levels, further exacerbate these disparities. Telemedicine has emerged as a potential solution, improving healthcare access in remote areas. However, its effectiveness is hindered by digital literacy gaps, infrastructure limitations, and privacy concerns. Policy interventions, including equitable healthcare funding, rural physician incentive programs, and enhanced digital health literacy initiatives, are crucial to addressing these challenges. Future research should explore scalable solutions for telemedicine implementation, assess the long-term impact of healthcare policy reforms, and develop integrated strategies to enhance healthcare accessibility in underserved communities. Ensuring equitable healthcare access remains a critical goal for global health systems, necessitating collaborative efforts from policymakers, healthcare providers, and technology developers.